A randomised controlled trial of acceptance and commitment therapy plus usual care compared to usual care alone for improving psychological health in people with motor neuron disease (COMMEND): study protocol - Rebecca L. Gould; Benjamin J. Thompson; Charlotte Rawlinson; Pavithra Kumar; David White; Marc A. Serfaty; Christopher D. Graham; Lance M. McCracken; Matt Bursnall; Mike Bradburn; Tracey Young; Robert J. Howard; et al. (BMC Neurology, 2022)
Abstract Background Motor neuron disease (MND) is a rapidly progressive, fatal neurodegenerative disease that predominantly affects motor neurons from the motor cortex to the spinal cord and causes progressive wasting and weakening of bulbar, limb, abdominal and thoracic muscles. Prognosis is poor and median survival is 2–3 years following symptom onset. Psychological distress is relatively common in people living with MND. However, formal psychotherapy is not routinely part of standard care within MND Care Centres/clinics in the UK, and clear evidence-based guidance on improving the psychological health of people living with MND is lacking. Previous research suggests that Acceptance and Commitment Therapy (ACT) may be particularly suitable for people living with MND and may help improve their psychological health. Aims To assess the clinical and cost-effectiveness of ACT modified for MND plus usual multidisciplinary care (UC) in comparison to UC alone for improving psychological health in people living with MND. Methods The COMMEND trial is a multi-centre, assessor-blind, parallel, two-arm RCT with a 10-month internal pilot phase. 188 individuals aged ≥ 18 years with a diagnosis of definite, laboratory-supported probable, clinically probable, or possible familial or sporadic amyotrophic lateral sclerosis, and additionally the progressive muscular atrophy and primary lateral sclerosis variants, will be recruited from approximately 14 UK-based MND Care Centres/clinics and via self-referral. Participants will be randomly allocated to receive up to eight 1:1 sessions of ACT plus UC or UC alone by an online randomisation system. Participants will complete outcome measures at baseline and at 6- and 9-months post-randomisation. The primary outcome will be quality of life at six months. Secondary outcomes will include depression, anxiety, psychological flexibility, health-related quality of life, adverse events, ALS functioning, survival at nine months, satisfaction with therapy, resource use and quality-adjusted life years. Primary analyses will be by intention to treat and data will be analysed using multi-level modelling. Discussion This trial will provide definitive evidence on the clinical and cost-effectiveness of ACT plus UC in comparison to UC alone for improving psychological health in people living with MND. Trial registration ISRCTN Registry, ISRCTN12655391. Registered 17 July 2017, https://www.isrctn.com/ISRCTN12655391 . Protocol version: 3.1 (10/06/2020).